Effect of postactivation potentiation on dynamic knee extension performance - Gossen, E. Roderich; Sale, Digby G. (European journal of applied physiology, 2000)
Six men and four women performed, in separate trials, maximal dynamic knee extensions with loads of 15%, 30%, 45% and 60% of maximal isometric knee extension peak torque (MVC). The dynamic extensions were done after postactivation potentiation (PAP) had been induced with a 10-s MVC, and in a control trial without PAP. PAP, measured as the increase in evoked twitch torque, was 53 (4)% (SE) and 43 (3)% at the time of the first and second extensions with each load. PAP failed to increase the attained peak velocity with any load; on the contrary, there was a trend for peak velocity to decrease in the first extension, which occurred approximately equal to 15 s after the 10-s MVC. The results suggest that fatigue produced by the 10-s MVC suppressed any benefit that could be derived from the induced PAP. A surface electromyogram (EMG) recorded from one muscle of quadriceps femoris gave no indication of activation failure in the first knee extension; however, activation impairment specific to the rate of force development cannot be ruled out. It is concluded that the strategy employed, namely of having knee extensions performed soon after the 10-s MVC to maximize PAP at the time of performance, was unsuccessful because there had been insufficient time for recovery from fatigue. It is possible that a longer recovery time, even at the cost of a diminished PAP, may have proved beneficial.